Influence of defect clusters on diffusion processes in UO2+x - Riahi, Fatma; Mekki, Djamel Eddine (Diffusion Fundamentals, 2009)
Thermodynamic and transport properties of hyperstoichiometric uranium dioxide,UO2+x, constitute a key issue in the application of this material for nuclear fuel since they are closely related to many chemical and physical processes, e.g., diffusion or creep. Starting from a point defect model for UO2+x developed by the authors in a preceding work[1] and quantitatively consistent with some literature experimental measurements of deviation from stoichiometry [2] and electrical conductivity[3],the oxygen and uranium self diffusion processes have been studied in order to appreciate the influence of defects involved in the model and particularly, the two Willis complexes i.e., 2(Oi"Oi''Vȯ)" and 2(Oi"O1''Vȯ)4''. Such a result leads the way to a better understanding of the mechanisms involved in diffusion processes and also helps to define more accurately the nature, as well as the type of the preferential interactions between diffusing impurities and the defects responsible for these transport properties.